2015 IEEE Virtual Reality (VR) 2015
DOI: 10.1109/vr.2015.7223327
|View full text |Cite
|
Sign up to set email alerts
|

Virtual proxemics: Locomotion in the presence of obstacles in large immersive projection environments

Abstract: Figure 1: Experimental conditions considered on the collision avoidance experiment. We analyzed the participants' avoidance behavior for real (left) and virtual objects (right), considering anthropomorphic and inanimated objects. ABSTRACTIn this paper, we investigate obstacle avoidance behavior during real walking in a large immersive projection setup. We analyze the walking behavior of users when avoiding real and virtual static obstacles. In order to generalize our study, we consider both anthropomorphic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 16 publications
6
40
2
Order By: Relevance
“…Similar results were also reported by Fink et al (2007). More recently, Sanz et al (2015) similarly compared clearance distances in virtual environments using a stereoscopic immersive projection space. They also found increased distance in the virtual space and increased distance when a static anthropomorphic representation was used, rather than an inanimate object.…”
Section: Proxemicssupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results were also reported by Fink et al (2007). More recently, Sanz et al (2015) similarly compared clearance distances in virtual environments using a stereoscopic immersive projection space. They also found increased distance in the virtual space and increased distance when a static anthropomorphic representation was used, rather than an inanimate object.…”
Section: Proxemicssupporting
confidence: 80%
“…Whilst some existing work has considered the use of crowd simulations in virtual reality (VR) settings, it has generally focused on three areas: firstly, the validation of simulation models by a human observer (Ahn et al 2012;Kim et al 2016;Pelechano et al 2008a, b;Rojas and Yang 2013;Rojas et al 2014); secondly, investigations of additional human-agent interactions, such as gestures and gaze (Kyriakou et al 2016;Narang et al 2016); and finally, user response to agent proximity (proxemics). Proxemics is of most relevance to our work, but existing investigations use 1 3 single agents or objects, or small groups in predefined configurations, rather than full crowd simulation models (Bruneau et al 2015;Llobera et al 2010;Wilcox et al 2006;Sanz et al 2015), and also use physiological measures of arousal rather than measures of affect.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of our study is to investigate the user's behavior and their subjective perception of realism, concentrating on the degree of interaction between the user and the virtual crowd, focusing on two main crowd behavior characteristics: collision avoidance, and basic social interaction (such as salutation and gaze) between the virtual crowd and the participant. Here, we include collision avoidance because it has been the main concerns of the crowd navigation methods that generate the low‐level crowd behavior,, Also, in a recent study, it was found that users acted differently (decrease of walking speed, increase of the clearance distance) when they had to avoid collisions with virtual humans than with other inanimate objects. Our hypothesis is that the level of interactivity of a virtual crowd towards the immersed participants would have an impact on participants' felt level of presence and their performance in VR.…”
Section: Related Workmentioning
confidence: 99%
“…Argelaguet, Olivier, Bruder, Pettr e, and L ecuyer (2015), for example, showed differences in proxemics behaviour between real and virtual environments. Argelaguet, Olivier, Bruder, Pettr e, and L ecuyer (2015), for example, showed differences in proxemics behaviour between real and virtual environments.…”
mentioning
confidence: 99%
“…Virtual and real environments are not only perceived differently, they also afford different behaviour. Argelaguet, Olivier, Bruder, Pettr e, and L ecuyer (2015), for example, showed differences in proxemics behaviour between real and virtual environments. On the one hand, it is fortunate that most people can draw a clear line between gameplay in VR and real-world interactions.…”
mentioning
confidence: 99%